Prohibition of Discrimination - Laczkó, Réka (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This study analyses the prohibition of non-discrimination within the framework of the European Convention on Human Rights, focusing thus on Article 14 of the Convention and Article 1 of Protocol No. 12. To facilitate a comprehensive understanding, the study will first provide a concise overview of the relationship between these provisions and other international instruments, particularly those adopted within the European context, followed by a brief examination of the historical evolution of the prohibition of discrimination. Subsequently, the analysis will delve into the scope of the provisions, the elements of discrimination, its various forms, and the conditions under which it operates, all considered in light of the jurisprudence of the European Court of Human Rights. In supporting the theoretical explanations, the study will prioritise the case law concerning Central and Eastern European countries. Keywords: Prohibition of discrimination, Article 14, Protocol No. 12, European Court of Human Rights